Customer-driven supply chains : From glass pipelines to open innovation networks - Lyons, Andrew C. (Decision Engineering, 2012)
In recent years, the supply chain has become a key element to the survival and prosperity of organisations in different industry sectors. Organisations dealing in dynamic business environments demand supply chains that support the satisfaction of customer needs. The principles of lean thinking that once permeated standalone organisations have now been transferred to the supply chain, making imperative the development of innovative approaches to supply chain management.    Customer-Driven Supply Chains: From Glass Pipelines to Open Innovation Networks reviews the concept of lean thinking and its relationship to other key initiatives associated with supply chain management. Detailed industrial case studies based on the authors' experience illustrate the principles behind lean supply chains. Moreover, a series of diagrams are used to illustrate critical concepts and supply chain architectures. Special emphasis is placed on the importance of transferring lean principles from the organisational level to the supply chain level. The theory and principles behind lean supply chains are reviewed. Other concepts related to lean supply chains discussed in the book include: mass customisation, agility, information sharing and the bullwhip effect. A methodology used to measure the performance of supply chains is introduced; this methodology comprises the tools of decision timeline, data-flow diagramming, supply chain value stream mapping and a performance measurement scorecard.   Readers will gain a clear picture of the competitive implications of lean supply chains. Customer-Driven Supply Chains: From Glass Pipelines to Open Innovation Networks will be a valuable resource of material to students studying supply chain/operations management as well as researchers in this field. Industry practitioners will learn how to develop sound supply chain strategies that can have a positive impact in their organisation.